2022
DOI: 10.1371/journal.pone.0268155
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and microbiota analyses of the oral cavity during psychological stress

Abstract: Psychological stress is associated with various oral diseases such as aphthous stomatitis, oral lichen planus, taste disturbances and glossodynia. However, the underlying mechanism is still unknown. The aim of this study was to determine the effect of psychological stress on salivary proteins and the oral microbiota in a rat model of chronic restraint stress. Six-week-old Sprague Dawley rats were subjected to restraint stress for four hours daily for 1 month. The behavior, weights of the adrenal glands, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…No significant differences in the beta diversities of the oral microbiome were observed between anxiety and depression patients with high and low symptoms [66] . A separate, but statistically non-significant, clustering was observed between the stress and control groups in an in vivo experiment using a rat model of chronic restraint stress [61] . However, a clinical study performing a constrained analysis of the oral microbiome reported significant clustering between the healthy and depressed cohorts [62] .…”
Section: Psychological Stress and Oral Microbesmentioning
confidence: 82%
See 4 more Smart Citations
“…No significant differences in the beta diversities of the oral microbiome were observed between anxiety and depression patients with high and low symptoms [66] . A separate, but statistically non-significant, clustering was observed between the stress and control groups in an in vivo experiment using a rat model of chronic restraint stress [61] . However, a clinical study performing a constrained analysis of the oral microbiome reported significant clustering between the healthy and depressed cohorts [62] .…”
Section: Psychological Stress and Oral Microbesmentioning
confidence: 82%
“…Thus, using an animal model might overcome the differences in local and systemic factors as seen in humans and provide reliable data on the alterations in the oral microbiome due to psychological stress. In our recent study comprising a rat model of chronic restraint stress, 16 S rRNA sequencing of oral microbiota revealed that the alpha diversity as measured by observed operational taxonomic unit and faith phylogenetic diversity was significantly lower in the stress group when compared to that in the control group [61] . Consistent with our findings, a previous experiment on wild red squirrels showed that the alpha diversity of the oral microbiome was lower in those with elevated fecal glucocorticoid metabolites, a measure of the hypothalamic-pituitary-adrenal axis [60] .…”
Section: Psychological Stress and Oral Microbesmentioning
confidence: 89%
See 3 more Smart Citations